2019
DOI: 10.3389/fphys.2019.01378
|View full text |Cite
|
Sign up to set email alerts
|

Differential Coping Strategies in Response to Salinity Challenge in Olive Flounder

Abstract: To examine how different fish coping strategies respond to salinity challenge, olive flounder (Paralichthys olivaceus) with active coping style (AC) and passive coping style (PC) were transferred from seawater (SW) to freshwater (FW) and their behavior and physiology were analyzed. Different behavioral coping strategies, in terms of escape and feeding tendencies, were confirmed in AC and PC fish without FW exposure. Differences in swimming distance between AC and PC flounder were then assessed after 1 and 2 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Mice in the passive group had a higher number of tumour focal, higher corticosterone levels and lower NKG2D receptor expression than mice in the active group (Azpiroz et al, 2008). When studying fish, it was found that there are differences in swimming, metabolism and osmotic pressure of zebrafish or flounder with different behaviours after salinity stress, suggesting that there are differences in coping strategies between the two types of fish under salinity stress (Yuan et al, 2018; Zeng et al, 2019). This study showed that the immune system of BI did not change significantly compared with BOT during acute cold stress, but the immune system of SI changed significantly compared with SOT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice in the passive group had a higher number of tumour focal, higher corticosterone levels and lower NKG2D receptor expression than mice in the active group (Azpiroz et al, 2008). When studying fish, it was found that there are differences in swimming, metabolism and osmotic pressure of zebrafish or flounder with different behaviours after salinity stress, suggesting that there are differences in coping strategies between the two types of fish under salinity stress (Yuan et al, 2018; Zeng et al, 2019). This study showed that the immune system of BI did not change significantly compared with BOT during acute cold stress, but the immune system of SI changed significantly compared with SOT.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific individual differences are a common phenomenon in the animal kingdom. Many research results show that the stable individual differences in animals are closely related to their life‐history strategies (Long et al, 2021; Yuan et al, 2017; Zeng et al, 2019; Zou et al, 2019). This kind of stable behavioural difference between individuals is what researchers call ‘individuality’ in animals (Long et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, bold crabs were the first to disperse when habitat quality was reduced (Belgrad and Griffen, 2018). Bolder fish make more attempts to escape laboratoryinduced hypoxia (Brelin et al, 2005;Ferrari et al, 2016), salinity challenges (Zeng et al, 2019) or high ammonia concentrations (Gesto et al, 2020). Bold individuals are also better at avoiding or escaping fishing gear (Diaz Pauli and Sih, 2017).…”
Section: Challenging Situations Make Proactive Individuals Change Habmentioning
confidence: 99%